2024
DOI: 10.3389/fgene.2024.1353289
|View full text |Cite
|
Sign up to set email alerts
|

Linkage mapping and genomic prediction of grain quality traits in tropical maize (Zea mays L.)

Noel Ndlovu,
Rajashekar M. Kachapur,
Yoseph Beyene
et al.

Abstract: The suboptimal productivity of maize systems in sub-Saharan Africa (SSA) is a pressing issue, with far-reaching implications for food security, nutrition, and livelihood sustainability within the affected smallholder farming communities. Dissecting the genetic basis of grain protein, starch and oil content can increase our understanding of the governing genetic systems, improve the efficacy of future breeding schemes and optimize the end-use quality of tropical maize. Here, four bi-parental maize populations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…The absence of QTLs associated with GY and related traits on certain chromosomes in our analysis, compared to previous studies, highlights the complex interplay of genes and environmental pressures that significantly shape QTL identification in tropical maize. The observed disparities can be attributed to distinct maize populations and growing/management conditions employed (Ndlovu et al, 2024). This further emphasizes the need to consider these prevailing interactions when investigating genetic influences on maize traits under WS conditions.…”
Section: Multiple Qtls Identified For Well-watered and Water-stressed...mentioning
confidence: 99%
See 2 more Smart Citations
“…The absence of QTLs associated with GY and related traits on certain chromosomes in our analysis, compared to previous studies, highlights the complex interplay of genes and environmental pressures that significantly shape QTL identification in tropical maize. The observed disparities can be attributed to distinct maize populations and growing/management conditions employed (Ndlovu et al, 2024). This further emphasizes the need to consider these prevailing interactions when investigating genetic influences on maize traits under WS conditions.…”
Section: Multiple Qtls Identified For Well-watered and Water-stressed...mentioning
confidence: 99%
“…Genomic prediction offers an alternative and complementary tool to achieve high selection efficiency with optimum resources (Beyene et al, 2015(Beyene et al, , 2019(Beyene et al, , 2021Atanda et al, 2021). Several studies reported that genomic-prediction-based models are effective in identifying betterperforming genotypes for GY and other agronomic and disease resistance traits (Crossa et al, 2017;Sitonik et al, 2019;Ertiro et al, 2020;Kibe et al, 2020a;Gowda et al, 2021;Ndlovu et al, 2022;Kimutai et al, 2023;Ndlovu et al, 2024). The effectiveness of GS compared to traditional phenotypic selection plays a significant role in determining its likelihood of adoption in breeding programs (Beyene et al, 2019;Kibe et al, 2020b).…”
Section: Genomic Prediction Accuracies Under Different Water Regimesmentioning
confidence: 99%
See 1 more Smart Citation